DAMPAK URBANISASI TERHADAP PERTUMBUHAN EKONOMI KOTA DI INDONESIA - Chandrika Febri Riyani; Muhammad Hanik Niyar; Nur Oriana Farkhatun Khoiriyah; Reva Agustin; Yoiz Shofwa Shafrani (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Urbanization is major factor influecing the economic growth of cities in Indonesia. This article examines how the migration of people from rural to urban araes drives productivity, economic diversification, and infracstructure invesment. Howevwer, urbanization also pressure on public sevices. Using a literature-based approach, this study explores the relationship between urbanization and economic growth, as well as strategies to manage urbanization for balanced development between rural and urban areas. The study results indicate that urbanization can effectively contribute to economic growth if managed properly through sound and sustainable policies.